Being a leader in a rhythmic interaction activates reward-related brain regions. (August 2019) - Sabu, Hiroka; Morita, Tomoyo; Takahashi, Hideyuki; Naito, Eiichi; Asada, Minoru
Highlights: Interpersonal rhythmic interaction is a fundamental social behavior. fMRI was used to measure brain activity during an alternating drum-hitting task. Most participants preferred the condition in which their hitting pace was copied. The sense of being followed activates reward-related brain regions. Being a leader in a rhythmic interaction task might be pleasant for humans. Abstract: Interpersonal rhythmic interaction is one of the fundamental behaviors that allow humans to socially interact with others. In this study, we provide novel neuroimaging evidence that being followed by other agents in such an interaction is pleasant for humans. Using functional magnetic resonance imaging, we measured the brain activity of 17 participants while they performed a virtual drum-hitting task, in one of the following conditions: a) alternating with a virtual agent that would always copy their hitting pace, or b) alternating with a virtual agent that would randomly hit the drum. The participants reported a significantly higher subjective feeling of being followed by the agent in the first condition. Moreover, almost all participants preferred the agent that followed their drum-hitting rhythm. The activity of the caudate nucleus, which is one of the reward-related brain structures, was found to be associated with the subjective feeling of being followed, suggesting that the sense of being the leader, in an interpersonal rhythmic interaction, creates a pleasant feeling.